1979
DOI: 10.1121/1.382240
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of sound production and air recycling in delphinids: Cineradiographic evidence

Abstract: Soft tissue silicone-casting techniques, spot-film radiography and cineradiography were combined to examine the in situ anatomy and movement of the upper airway structures in live-phonating and dead delphinid porpoises. Three species, Tursiops truncatus, Tursiops gilli, and Stenella longirostris were studied under high-speed x-ray motion picture cameras to observe the movements in the laryngeal and nasal regions associated with sound production. Accurate reconstructions of the nasal sac anatomy were made by as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 0 publications
4
65
1
Order By: Relevance
“…During a typical click train, the subject's source levels followed a stereotypical pattern, starting at low source levels, increasing to a maximum, and then decreasing towards the end of the click train (Fig.3). This pattern is common for echolocating odontocetes (Au et al, 1974;Au et al, 1987) and is thought to be a result of the pneumatic generating process (Norris and Harvey, 1972;Dormer, 1979;Ridgway et al, 1980;Amundin and Andersen, 1983). The whale also used a scanning motion with her head and echolocation beam, clicking first off-axis, then directly on the target, and again scanning off-axis.…”
Section: Methodsmentioning
confidence: 99%
“…During a typical click train, the subject's source levels followed a stereotypical pattern, starting at low source levels, increasing to a maximum, and then decreasing towards the end of the click train (Fig.3). This pattern is common for echolocating odontocetes (Au et al, 1974;Au et al, 1987) and is thought to be a result of the pneumatic generating process (Norris and Harvey, 1972;Dormer, 1979;Ridgway et al, 1980;Amundin and Andersen, 1983). The whale also used a scanning motion with her head and echolocation beam, clicking first off-axis, then directly on the target, and again scanning off-axis.…”
Section: Methodsmentioning
confidence: 99%
“…Later, it was shown that most soundsare produced in the nasal region (Diercks et al, 1971;Hollien et al, 1976;Dormer, 1979;Mackay and Liaw, 1981;Amundin and Andersen, 1983), but the exact location and mechanism remained unknown. In 1997, Cranford and colleagues described results of using an endoscopy to examine sound generation in a bottlenose dolphin (Tursiops truncatus).…”
Section: Echolocation and Sound Sourcesmentioning
confidence: 99%
“…Whistles and burst-pulsed sounds can be produced simultaneously (Janik, 2009). This corresponds with the generally accepted concept that there are two sites of sound production that can be controlled independently (Dormer, 1979). They are composed of two identical sound producing structures consisting of fatty dorsal bursae within a pair of phonic lips, one in the left and one in the right nasal passage (Cranford et al, 1996).…”
Section: Behavioral Data On Auditionmentioning
confidence: 99%